Antioxidant and anti-inflammatory potentials of the leaf extracts of Calotropis procera and Enantia chlorantha - Ogunjinmi, Oluwasayo Esther; Adegbola, Peter Ifeoluwa; Odedele, Johnson Oladimeji; Adedokun, Ganiyat Adeyinka (European Journal of Chemistry, 2024)
Inflammation and oxidative stress are involved in the aetiology of numerous human diseases. The two processes are interconnected such that one may appear before or after the other, but as soon as one of them appears, the other will. Consequently, targeting the two conditions may aid in the prevention or treatment of associated human diseases, and plants capable of performing the two functions together are of great advantage. This study was aimed at evaluating the antioxidant and anti-inflammatory potentials of methanol and aqueous extracts of Calotropis procera and Enantia chlorantha. The leaves of the two plants were extracted separately in water and methanol using a cold maceration method. Antioxidant activity was evaluated using the Lipid peroxidation (LPO), 1,1-diphenyl-2-picrylhydrazyl (DPPH), and ferric reducing antioxidant power (FRAP), while the anti-inflammatory properties were evaluated using membrane stabilization and inhibition of protein denaturation assays. Qualitative phytochemical analysis was performed using standard methods. The results of the study showed that the aqueous extract of the two plants demonstrated better antioxidant activity than the methanol extracts. IC50 values of 61.60, 59.12, and 83.07 µg/mL were, respectively, for ascorbic acid, aqueous extracts of E. chlorantha and C. procera, while the methanol extracts of both plants recorded a value >150 µg/mL for DPPH. For LPO inhibition, the IC50 values were 191.79 µg/mL, >150 µg/mL for the aqueous, methanol extracts of C. procera and 228.25 µg/mL, 135.46 µg/mL for ascorbic acid and quercetin used as standards. The aqueous extract of E. chlorantha had a value of 161.95 µg/mL and the methanol extracts had a value >250 µg/mL. For the two anti-inflammatory methods used, the IC50 values for the plant were >250 µg/mL. Phytochemicals such as tannins, flavonoids, alkaloids, terpenoids, and phenols were identified in both plant samples. Overall, the results demonstrated the potential of the plant when used for the treatment of diseases related to inflammatory and oxidative stress.